2013
DOI: 10.1002/jts.21768
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for Change Predicts VA Mental Healthcare Utilization Among Iraq and Afghanistan War Veterans

Abstract: Many veterans present to Veteran Affairs (VA) care intending to seek mental health treatment for symptoms of posttraumatic stress disorder (PTSD), depression, and/or alcohol misuse, yet most subsequently underutilize mental health care. This study examined the association of readiness for change with outpatient VA mental health care utilization in 104 treatment-seeking Iraq and Afghanistan war veterans who screened positive for PTSD, depression, and/or alcohol misuse at intake. Multivariate analyses demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Our findings highlight that timely service provision within the brief intervention and through referrals to long‐term services led to prompt attention to acute and chronic health conditions, relieved stress, and encouraged hopefulness and motivation to sustain engagement in the help‐seeking process. Conceptual models of recovery consistently highlight the importance of hope and goal‐setting (Leamy, Bird, Boutillier, Williams, & Slade, ; Mead & Copeland, ), and evidence indicates that internal motivation is an important predictor of reduced substance use (Collins, Malone, & Larimer, ) and mental health service utilisation (Jakupcak et al., ). While there is little evidence supporting any specific strategies to increase hopefulness, some qualitative work has suggested that experiences of success are generally helpful (Schrank, Bird, Rudnick, & Slade, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight that timely service provision within the brief intervention and through referrals to long‐term services led to prompt attention to acute and chronic health conditions, relieved stress, and encouraged hopefulness and motivation to sustain engagement in the help‐seeking process. Conceptual models of recovery consistently highlight the importance of hope and goal‐setting (Leamy, Bird, Boutillier, Williams, & Slade, ; Mead & Copeland, ), and evidence indicates that internal motivation is an important predictor of reduced substance use (Collins, Malone, & Larimer, ) and mental health service utilisation (Jakupcak et al., ). While there is little evidence supporting any specific strategies to increase hopefulness, some qualitative work has suggested that experiences of success are generally helpful (Schrank, Bird, Rudnick, & Slade, ).…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds with the 10-year increase in income observed for our respondents. The growing effort to incorporate brief interventions, including motivational interviewing, in general medical care is one possible avenue to improve perception of need and treatment utilization (Dawson et al, 2012; Jakupcak et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Initial results using brief motivational feedback have shown that veteran patients with comorbid substance dependence and psychiatric disorder were more likely to enter outpatient treatment groups compared to those veterans who did not receive brief motivational feedback (Lozano, LaRowe, Smith, Tuerk, & Rotzsch, 2013). Likewise, combat veterans who indicated a readiness for change at intake were more likely to utilize outpatient mental care resources (Jakupcak et al, 2013). …”
Section: Psychological Health Research Continuummentioning
confidence: 99%